COLLLABORATIVE STRATEGIC READING (CSR) IN THE EFFECTIVENESS OF TEACHING READING COMPREHENSION - Muhabibah Nur Reformista; Zanubah Arifah Khofshoh (FKIP, Universitas Billfath Lamongan, 2022)
This research aims to determine the effectiveness of using CSR technique in teaching reading comprehension at Class IXB MTs. Miftahul Jinan Glugu. This research method is quantitative descriptive with pre-experimental research design, this research in the form of one group pre-post-test. Based on the results of the pre-test it got an average score of 51.58, increasing in the post-test with an average score of 82.11. And then at table of the pair-sample t-test with the basis for making decisions, namely if sig. (2-tailed) < 0.05 then H0 is rejected and Ha is accepted. The result of the value of sig. (2-tailed) in this research is 0.000 <0.05, then H0 is rejected and Ha is accepted. The results of this research can be concluded that CSR technique is effective in teaching reading comprehension at class IXB MTs. Miftahul Jinan Glugu.